The Psychological Health and Work-Family Balance of Ambulatory Care Nurses in the COVID-19 era: A Cross-Sectional Survey - Girard, Ariane; Carrier, Jean-Daniel; Poitras, Marie-Eve; Cormier, Caroline; Lesage, Alain; Berbiche, Djamal; T. Vaillancourt, Vanessa (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2022)
Introduction: The COVID-19 pandemic impacted nurses’ psychological health and work-family balance, including in ambulatory care settings. The results presented in this article are part of a study aiming to describe and contextualize the psychological health and changes in nurses’ follow-up practices in Quebec (Canada) during the COVID-19 pandemic.Objective: Explore and describe factors that influenced ambulatory care nurses’ psychological health and work-family balance during the first wave of the COVID-19 pandemic.Methods: Exploratory mixed data cross-sectional study using the SurveyMonkey platform. We collected data from July 2020 to September 2020. The target population comprised all practicing nurses in Quebec whose clinical activities included the follow-up of ambulatory patients, 200 of whom completed the survey. Results: Multiple linear regression models indicated that anxiety (GAD-7 scores) and depressive symptoms (PHQ-9 scores) were associated with younger age, living alone, worries about transmitting COVID-19, and feeling that one’s work was not coherent with one’s values. Work-family balance was considered more difficult than before the pandemic by 54.5 % of participants. Factors perceived as influencing work-family balance were either related to work conditions (e.g., schedule and time at work, access to work from home, redeployment to another work setting), to family-related responsibilities/tasks or were specific to the pandemic.Discussion and conclusion: Apart from age, the feeling that one’s work was not coherent with their values was the only variable correlated with both GAD-7 and PHQ-9 in multivariate models. Further research should investigate the relationships between sense of coherence, psychological health, and work conditions like schedule flexibility and access to work from home.